PENGARUH GOOD CORPORATE GOVERNANCE, STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN - Tambunan, Ronia - (Universitas YPPI Rembang, 2023)
This study aims to determine the effect of audit committees, managerial ownership and company size on the financial performance of transportation and logistics companies listed on the IDX for the period 2018 – 2021. The study population is a company engaged in the transportation and logistics sector by selecting the sample through a purposive sampling method. There are 8 companies that meet the criteria as research samples. Data analysis techniques using simple linear regression analysis, and multiple linear regression analysis. The research results show that good corporate governance (proxied by audit committees and managerial ownership), capital structure and company size have no effect on financial performance. Keywords: Good Corporate Governance, Capital Structure, Company Size, Financial Performance